Visual representation of the Oirat-Kalmyks and Tuvans in the context of power relations - Chetyrova, Lyubov B.; Sergeeva, Nataliya M. (The New Research of Tuva, 2023)
The article examines the issue of visual representation of the Oirat-Kalmyks and Tuvans in the context of power relations. The methodological basis of the study is the decolonial theory; the authors also use visual analysis methods. It is assumed that in their form and content, visual representations of the Oirat-Kalmyks and Tuvans contain hidden and explicit signs indicating the specific character of their relations with the Russian authorities. The source base of the research comprises visual documents of the imperial period stored in the Astrakhan State United Historical and Architectural Museum-Reserve, the National Archives of the Republic of Tuva and in the private collection of S. Yu. Stepanov (Astrakhan, Russia). The first section of the article presents a study of the history of the representation of foreigners in the Russian Empire; it is considered how the visualization of subjects of the multi-ethnic empire was carried out at the All-Russian Ethnographic Exhibition of 1867. The authors conduct a research on when such a visualization first occurred — namely, thanks to the famous Ice House. By using historical materials dedicated to the Kalmyk Khan Donduk-Ombo, it is proved that the Ice House was not just a wedding of two court jesters, but a project ensuring that such a representation was carried out. In such a way, they determined places of outlanders in the colonial hierarchy. The second section gives an analysis of photographs containing markers that fix the place of the Oirat-Kalmyks in their relations with the authorities, taking into account the described historical context. The analysis of visual documents representing the Oirat-Kalmyks reveals the strategy of symbolic submission used by the imperial power and the tactics of symbolic resistance and disobedience on the part of the Oirat-Kalmyks. The imperial representation of the Oirat-Kalmyks is largely provided by their images on postcards, which look theatrical, emphasize the otherness of the Kalmyks, make them an object of consideration and comparison with the majority (the Russians) whose tokens in the form of household items are also present in the composition in almost all cases. The third section considers the visual representations of the Tuvans during their entry into the protectorate of Russia. These representations look like photographic reports from the scene of an event that were made in natural living conditions, without the use of retouching and compositional designation of the superior or, on the contrary, subordinate position of this people. Here both the form and content of representations indicate exceptional, in comparison with the emphatically objectified Oirat-Kalmyks, relationship between the Russians and Tuvan nomads. Representatives of the ruling elite of Tuva are portrayed as truly independent, self-determined, connected with the imperial authorities as partners. Thus, the Tuvan visual case not only illustrates the specific features of the real history of integration between the Tuvans and the Russians, but also highlights the policy of “otherness” in relation to Kalmyk nomads by contrast.